2014
DOI: 10.3221/igf-esis.30.52
|View full text |Cite
|
Sign up to set email alerts
|

Interlaminar fracture in woven carbon/epoxy laminates

Abstract: This paper describes an experimental study developed to characterize the mode I and mode II fracture toughness of carbon/epoxy woven composites, using DCB and ENF tests, respectively. The laminates were manufactured using an epoxy resin and twelve woven balanced bi-directional layers of carbon fibres, all of them with the same orientation (0/90º). Significant instantaneous delaminations were observed particularly for the DCB specimen, which were responsible for an oscillatory behaviour of G I versus crack leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This behavior of GIc is similar to that of other studies reported in the literature. 5,27 Specimens 1 and 5, failed dramatically before reaching a crack length of 98.75 mm. Hence, the GIc of these specimens was shown to a crack length of 68.75 mm and 78.75 mm, respectively.…”
Section: B Dcb Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior of GIc is similar to that of other studies reported in the literature. 5,27 Specimens 1 and 5, failed dramatically before reaching a crack length of 98.75 mm. Hence, the GIc of these specimens was shown to a crack length of 68.75 mm and 78.75 mm, respectively.…”
Section: B Dcb Resultsmentioning
confidence: 99%
“…4 Lecturer, University of Limerick, ronan.ohiggins@ul.ie. 5 Bernal Chair in Composite Materials and Structures, University of Limerick and AIAA Member, paul.weaver@ul.ie.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, both curves possessed similarities of at least 98.8%. The gradient of the unidirectional curve ( m ) resulted in a G IIc value of approximately 1175.85 J m −2 , while equations suiting the woven specimen which were described by Reis et al 22 produced a G IIc value of approximately 1408.11 J m −2 .…”
Section: Resultsmentioning
confidence: 99%
“…Several analytical methods were implemented to determine G IIc ; Reis et al utilised a modified crack length measure which was calculated from the specimen compliance. 22 Ogasawara et al used the more common conjugate beam analysis which takes the peak load and displacement into account. 26 Morais and Pereira fit the CC data to a third-order equation and using the resulting parameters calculated G IIc , 27 and the ASTM D7905 standard which was intended for unidirectional ENF specimens.…”
Section: Resultsmentioning
confidence: 99%
“…The 3-ENF method was originally proposed for testing, but was later developed into the S-ENF, T-ENF and 4-ENF methods [36]. However, according to Pereira et al., [37] the end-notched flexure test is the best method for Mode II testing, owing to its simplicity, negligible friction effects, and low tendency for geometric non-linearity [38].…”
Section: Interlaminar Fracture Toughnessmentioning
confidence: 99%